Inserção educacional, saúde mental e processamento cognitivo em crianças ouvintes filhas de pais surdos (CODAs) - Reis, Dulcilene Saraiva (2020)
This research aimed to present the peculiarities of bimodal bimodal children who are hearing and their parents are deaf, known as Coda. These children are considered natural bilinguals because they acquire two languages and are also considered bicultural, because they live between two cultures: deaf, due to living with their deaf parents, and hearing, because they share experiences with their hearing peers. The research was divided into two studies. Study 1 aimed to understand the process of educational insertion of the Coda child, as well as the emotional aspects associated with the experience of being a Coda, and Study 2 aimed to investigate the cognitive development of children Coda by evaluating the Overall Intelligence Quotient (IQ) and Executive Functions. The sample consisted of five Coda children aged between seven and eleven years, their deaf mothers and their teachers, four living in Porto Velho and one in Cacoal, in the state of Rondônia, and was carried out from 2018 to 2020. The results from Study 1 indicated that one of the greatest difficulties of Coda children is related to the acquisition of written language, as well as it was evidenced that the feeling of responsibility of children when acting as interpreters for their parents has caused emotional stress and anxiety. The results of Study 2 indicated that in the item Total IQ, the Coda children remained in the 7079 IQ range, presenting a lower performance and the performance result was lower average in the subtests of the execution area. However, in the subtests that assess verbal skills, most participants had a lower result, indicating a lot of difficulty in these skills. Regarding Executive Functions, the results indicated that most Coda children had difficulty performing the tests involving language, as well as demonstrated that most participants had no difficulty performing the Executive Functions tests related to attention, perception and memory, with emphasis on operational working memory. In arithmetic skills, all Coda children had an average result. Thus, the two studies made it possible to know the specificities of Coda children with regard to their cognitive development, educational insertion and emotional aspects.